PREDICTIVE RISK ASSESSMENT SCALE OF ISCHEMIC COLITIS DEVELOPMENT IN PATIENTS WITH ELECTIVE INFRARENAL AORTIC ANEURISM REPAIR - N. A. Yaitsky; A. Ya. Bedrov; A. A. Moiseev; G. V. Rybakov (Вестник хирургии имени И.И. Грекова)
The article presents the scale developed by authors of prognostic assessment of ischemic colitis evolution in patients after planned resection of infrarenal aortic aneurism. A retrospective analysis of medical histories of 201 operated patients and statistical data manipulation were made at the period from 1985 to 2016. It was stated, that score less than 2 points represents patients of high risk group of ischemic colitis development. The scale of sensitivity consisted of 80% and scale of specificity - 63,4%. The score of developed scale depended of passability and blood flow condition in the inferior mesenteric, the right and left internal iliac arteries being evaluated during surgery. The aim of surgeons is to increase the number of points in the scale using revascularization of the inferior mesenteric and at least one of internal iliac artery in patients of the high risk group of ischemic colitis development.